Foliar spraying of boron prolongs preservation period of strawberry fruits by altering boron form and boron distribution in cell - Zhang, Lei; Sun, Changgang; Tian, Hui; Xu, Jiamin; Wu, Xiuwen (Frontiers in Plant Science, 2024)
Boron (B), an essential micronutrient for fruit development, also plays a crucial role in maintaining the shelf life of strawberries (Fragaria ananassa Duch.) by affecting cell wall structure and components. We investigated the distribution pattern of B within cells and cell walls in strawberry fruits under different B levels and revealed the relationship between the B distribution in cell walls and fruit firmness after harvesting. Foliar spraying of 0.1% H3BO3 promoted the growth of strawberry seedlings and improved fruit yield and flesh firmness by 45.7% and 25.6%. During the fruit softening and decay process, the content of bound B and cell wall-B decreased while more B was allocated to the protoplast and apoplast. The changes in B distribution in cells were attributed to cell damage during fruit decay, and B extended the freshness period of the fruits by alleviating the decrease of B distribution in cell walls. After leaving the fruits at room temperature for 10 h, the B content in different cell wall components significantly decreased, while foliar spraying of B alleviated the reduction of B content in covalently bound pectin (CBP), cellulose, and hemicellulose. Meanwhile, B spraying on fruit decreased the activity of cell wall degradation enzymes, including polygalacturonase (PG) and pectin lyase (PL), by 20.2% and 38.1%, while enhancing the demethylation of pectin by increasing pectin methylesterase (PME) activity from 21.6 U/g to 25.7 U/g. Thus, foliar spraying of 0.1% H3BO3 enhances the cross-linking of B with cell wall components and maintains cell wall structure, thereby prolonging the shelf life of strawberry fruits.